2020
DOI: 10.1038/s41598-020-67785-x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of coastal upwelling after a plunge in upwelling-favourable wind

Abstract: Unprecedented coastal upwelling off the southern coast of the Korean Peninsula was reported during the summer of 2013. The upwelling continued for more than a month after a plunge in upwellingfavourable winds and had serious impacts on fisheries. This is a rare phenomenon, as most coastal upwelling events relax a few days after the wind weakens. In this study, observational data and numerical modelling results were analysed to investigate the cause of the upwelling and the reason behind it being sustained for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…During summer, wind-driven upwelling due to monsoonal southerly winds occurs at the east coast of Korea (Park and Kim, 2010;Jung and Cho, 2020;Kim et al, 2023). We thus expect climatological northward wind stress in that area (Figure 11A).…”
Section: H′ Anomaly In the Summer Of 2021mentioning
confidence: 92%
“…During summer, wind-driven upwelling due to monsoonal southerly winds occurs at the east coast of Korea (Park and Kim, 2010;Jung and Cho, 2020;Kim et al, 2023). We thus expect climatological northward wind stress in that area (Figure 11A).…”
Section: H′ Anomaly In the Summer Of 2021mentioning
confidence: 92%
“…The air pressure and relative humidity for the bulk-flux formula were set to constants of 1007.5 hPa and 86.7%, respectively. The ranges of wind speed, air temperature, and shortwave radiation were based on the upwelling conditions on the southern coast of the Korean Peninsula during the summer (Jung & Cho, 2020). Shortwave radiation was imposed using a diurnal cycle.…”
Section: Model Setupmentioning
confidence: 99%
“…However, a recent observational result demonstrated that the SST difference between the cold coastal and warm offshore regions increased during strong surface heating (Jung & Cho, 2020). A strong coastal upwelling along the southern coast of the Korean Peninsula was reported during the hot summer of 2013 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the surface sea water is swept away to the open ocean, and a CWM is formed by upwelling of the intermediate and deep-sea waters. These events can cause mass die offs in fisheries, or the formation of sea fog [ 21 ]. Kim et al have reported that an average of approximately 24 days of CWM has appeared every year for the past 7 years (2012 to 2018) along the southeastern coast and that the frequency tends to increase in June compared to that in July and August in accordance with the climatic changes such as the change in atmospheric pressure patterns, and the weakening of the monsoon [ 22 ].…”
Section: Introductionmentioning
confidence: 99%